An exclusive phonological method of teaching a foreign language with a professionally oriented approach - Rybakova, Lyudmila V.; Neverova, Natalia V. (Amazonia Investiga, 2023)
The relevance of the topic of the article is due to the reassessment of the goals and objectives of professionally oriented language education at the undergraduate level in the light of UNESCO initiatives. The hypothesis: use of the proposed methodology in the course of teaching English with the indicated approach at a technical university can significantly improve pronunciation. The purpose is to determine the effectiveness of the phonological methodology in teaching a foreign language based on a professionally oriented approach. Methodology: pilot experiment, comparison, observation, description, Wilcoxon's T-test, induction. The experiment in 2019-2020 involved 60 students of the Moscow Aviation Institute (National Research University). Most relevant results: repeated control testing revealed an increase in the level of foreign language proficiency. The Wilcoxon t-test confirmed the significance of differences in the results: Temp=0< Tcr (n=4; p?0.01)=1. Practical testing of this study showed that the vocalism technique provides effective opportunities for implementing an individual learning path. Thus, future research suggested by the results will continue to improve the phonology of pronunciation. The novelty of the study lies in the fact that this experiment was conducted for the first time at an aerospace non-linguistic university.